Pendidikan Islam dan Humanitas - Irrubai, Mohammad Liwa (Al-Riwayah : Jurnal Kependidikan, 2018)
Today, the human problem in social life concerning education is growing more complex; many new ideas emerge as the level of human intellectuality grows. This paper will reveal the current issue of education in Indonesia and discuss ideas from the concept of liberal education. The basic issue of education criticized by liberal education is that education today focuses more on the needs of society than the educational objectives themselves. Education as a tool to transfer science, values, and agents of social change is seen as one alternative solution in the framework of improving people's lives. The education in which values are embodied is one of the efforts offered by genuine liberal education, aimed at giving us the habits, ideas and techniques necessary to continue our own education. Humans have the ability to learn continuously throughout life so that we can prepare ourselves to study and again as long as we are alive